1988
DOI: 10.1246/bcsj.61.2047
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Synthetic Ionophores. VI. Synthesis of Polyether Carboxylic Acids and Their Use as Carriers for Alkali Metal Ion Transport through Liquid Membrane

Abstract: ω-Hydroxy carboxylic acids (3, 5, 6, 7, 10, 12, 14, 17, 18, 20, and 22) bearing 2–6 ether oxygens and aromatic rings with or without a tetrahydrofuran ring and the ω-methoxy and ω-benzyloxy derivatives of 5 (8 and 9) were synthesized. These were employed as carriers for active and competitive transport of alkali metal ions through liquid membrane as well as for extraction of alkali metal ions to organic layers. Effect of hydrophobic group of aromatic and tetrahydrofuran rings, number of ether oxygens, and term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Model compound (2) was synthesized using successive Williamson's methods (Kuboniwa et al, 1985). An ion-transport experiment using (2) through a ClCH 2 CH 2 Cl liquid membrane was carried out in a Utube apparatus as described previously (Yamaguchi et al, 1988), however, transported ions were analyzed by atomic absorption spectrometry instead of¯ame analysis. The analysis showed that 22% of Na + and 73% of K + were transported by (2) with errors of about 5% in 5 d. A solution of RbOH in MeOH (0.54 ml, 3.74 mM) was added to the solution of (2) (11.3 mg) in 20 ml MeOH and the mixture was stirred overnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model compound (2) was synthesized using successive Williamson's methods (Kuboniwa et al, 1985). An ion-transport experiment using (2) through a ClCH 2 CH 2 Cl liquid membrane was carried out in a Utube apparatus as described previously (Yamaguchi et al, 1988), however, transported ions were analyzed by atomic absorption spectrometry instead of¯ame analysis. The analysis showed that 22% of Na + and 73% of K + were transported by (2) with errors of about 5% in 5 d. A solution of RbOH in MeOH (0.54 ml, 3.74 mM) was added to the solution of (2) (11.3 mg) in 20 ml MeOH and the mixture was stirred overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Naturally occurring acid ionophores are known to mediate active ion transport through lipophilic membranes by formation of hydrophobic complexes with ions (Taylor et al, 1982, and references therein) and their structures were studied to provide information on their function (Duesler & Paul, 1983, and references therein). We have synthesized a series of relatively simple 3-hydroxycarboxylic acids as model compounds for the naturally occurring ionophores to investigate the relationship between the primary molecular structures and ion-transport properties (Kuboniwa et al, 1982(Kuboniwa et al, , 1985Yamazaki et al, 1978Yamazaki et al, , 1979Yamaguchi et al, 1988Yamaguchi et al, , 1989.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…4 were calculated by using Eqs. [3]- [6], respectively. The values of K a and u Na /u H obtained from the best fit of the theoretical curves with the experimental results in the range of low hydrogen ion concentration were 0.21 (mol dm Ϫ3 ) and 0.080, respectively.…”
Section: Fig 2 Diffusional Flux Of Namentioning
confidence: 99%
“…For the liquid membrane-aqueous electrolyte systems including an ionic carrier with weakly ionized groups, the ion permeation against the own concentration difference driven by pH difference has been investigated by many workers (1)(2)(3)(4)(5)(6). Moreover, it has been suggested that the incorporation of metal ions into the reversed micellar structure in the liquid membrane facilitate the ion permeation process (7,8).…”
Section: Introductionmentioning
confidence: 99%